(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
The physiology of breathing during sleep predisposes to the onset or worsening of breathing disorders in patients with metabolic syndrome (MS), even if their respiratory function remains relatively normal while awake. Respiratory pathology often causes insomnia, which further aggravates the impairment of the quality of life of patients. Long-term low-flow oxygen therapy and noninvasive assisted ventilation improve gas exchange during sleep but often do not improve sleep disturbances (4, 3,5,7).